Financial integration and entrepreneurial activity: evidence from foreign bank entry in emerging markets - Mariassunta Giannetti; Steven Ongena (European Central Bank (ECB), 2005)
An extensive empirical literature has documented the positive growth effects of equity market liberalization. However, this line of research ignores the impact of financial integration on a category of firms crucial for economic development, i.e. the small entrepreneurial firms. This paper aims to fill this void. We employ a large panel containing almost 60,000 firm–year observations on listed and unlisted companies in Eastern European economies to assess the differential impact of foreign bank lending on firm growth and financing. Foreign lending stimulates growth in firm sales, assets, and leverage, but the effect is dampened for small firms. We also find that firms started during the transition period of 1989-1993 – arguably the most connected businesses – benefit least from foreign bank entry. This finding suggests that foreign banks can help mitigate connected lending problems and improve capital allocation.
Keywords: G21; L11; L14; 330; competition; emerging markets; foreign bank lending; lending relationships; Entrepreneurship-Ansatz; Unternehmenserfolg; Internationale Bank; Kreditgeschäft; Wettbewerb; Schätzung; Osteuropa